The Prediction of Religiosity on Students’ Academic Dishonesty - Oktaviyani, Devi; Sunawan, Sunawan; Khairkhah, Khairuddin (Jurnal Pendidikan Agama Islam, 2022)
Purpose – Previous findings show that the relationship between students' levels of religiosity and academic dishonesty is inconsistent. The purpose of the present study is to clarify the relationship between religiosity with academic dishonesty. Design/methods/approach – This correlational research involved 251 students (60.6% female) of Madrasah Ibtidaiyah in Batang Regency, Central Java who were selected using cluster random sampling. Religiosity data was collected using the centrality of religiosity scale (TCR), and academic dishonesty data was assessed using the academic dishonesty scale (ADS). Data analysis was used using SPSS regression analysis. Findings – The results showed that religiosity predicted a decrease in academic dishonesty. This research also confirms that three dimensions of the 5 dimensions of religiosity significantly predict academic dishonesty, namely ideology, personal practice, and experience. The other two dimensions, namely intelligence and public practice, do not correlate with academic dishonesty. Research implications/limitations – These findings can strengthen collaboration between guidance and counseling teachers and religious education teachers to reduce students' academic dishonesty by strengthening students' levels of religiosity. Religiosity is not only seen as a ritual of worship. Originality/value – These findings have clarified and confirmed the relationship between religiosity and academic dishonesty, particularly the three dimensions of religiosity that contribute to explaining academic dishonesty.